Tiktokers: Studi Kasus Tentang Penerimaan Konsep Diri Yang Positif Pada Mahasiswa ITBK Bukit Pengharapan Tawangmangu - David Setiawan; Jonathan Hizkia Hosea Salendur (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
This article aims to look at the self-concept that is formed in Christian youth today with the lively development of TikTok social media. In forming a positive self-concept of young people, external factors are very influential. Of the many studies that have been conducted, many have found that a positive self-concept is influenced by the TikTok social media application for TikTokers. Based on these facts, it is necessary to conduct research on the causes of positive self-concept for today's youth, especially Christian youth. Through descriptive qualitative research with a literature study approach and field surveys, it can describe the causes of positive self-concept TikTokers ITBK Bukit Pengharapan Tawangmangu to be implemented for today's Christian youth. From this research, it was found that the positive self-concept of TikTokers ITBK Bukit Pengharapan is not affected by TikTok social media, but because TikTokers ITBK Bukit Pengharapan Tawangmangu are young people who have accepted Christ and live life to be like Christ.